An Analysis of Expressive Speech Acts Types in “The King’s Speech” - Dwi Wahyuningtyas; Sirniawati (Nusantara Science and Technology Proceedings, 2022)
People often give information or utter something where the words they utter are considered as an action. That is called “speech acts”. Speech acts have some types, one of which is the illocutionary speech act. Illocutionary acts consist of assertive, directive, commissive, expressive, and declarations. This study will focus on the use of expressive speech acts as this type of speech act is often found in some literary works such as drama and movies or films. The film that was chosen to be analyzed was “The King’s Speech”. The researchers studied the types of expressive speech acts in the movie. Descriptive qualitative was employed as the design of this study by using several approaches; mimetic, pragmatic, expressive, and objective. The findings revealed that there were expressive congratulating, expressive attitude, expressive wishing, expressive thanking, and expressive apologizing as types of expressive speech acts found in the film “The Kings’ Speech”.